Scrotal Lymphangiectasia with Penile Elephantiasis in Underlying Lymphatic Filariasis-Challenging the Diagnostic Mind! A Case Report - Tejas Vishwanath; Angela Nagpal; Sunil Ghate; Aseem Sharma (MDPI AG, 2021)
Background: A plethora of diseases manifest as acquired genital lymphangiectasias which clinically manifest as superficial vesicles. They range from infections such as tuberculosis to connective tissue diseases such as scleroderma and even malignancy. Amongst infectious etiologies, lymphatic filariasis leads as the cause for lymphatic obstruction. Despite this, acquired lymphangiectasias due to this cause are not commonly reported. An unusual case of acquired scrotal lymphangiectasia secondary to filariasis is detailed in this paper with dermoscopic and histologic findings. Methods: A 65-year-old male farmer presented with multiple, asymptomatic vesicles over the scrotum with thickened scrotal and penile skin that had occurred for six years. He gave past history of intermittent fever and milky urine, was diagnosed with filariasis and treated with diethylcarbamazine for a year, four years previously. Systemic complaints abated but the peno-scrotal lesions did not. Results: Polarized dermoscopy revealed multiple skin-colored nodules and translucent pale blue lacunae over the scrotum. A few radially arranged linear irregular vessels were noted over the nodules. On histopathology, multiple ectatic lymphatics were noted in the mid and upper dermis with acanthosis and superficial perivascular lymphocytes. Peripheral smear revealed eosinophils; however, microfilariae could not be detected despite repeated diethylcarbamazine provocation and night smears being taken. The findings were compatible with acquired scrotal lymphangiectasia secondary to treated lymphatic filariasis. Local hygiene was advised; however, procedural treatments were refused by the patient. Conclusion: Herein, we report an unusual case of acquired scrotal lymphangiectasia of the scrotum secondary to treated lymphatic filariasis. Very few similar reports exist. To the best of our knowledge, dermoscopic features of this condition have not been elucidated before. This case, detailing an uncommon manifestation of a common disease (filariasis), demonstrates the importance of careful history taking and examination. This was especially so in the present case since only circumstantial evidence of filariasis was noted in investigations. There is a need to heighten awareness of this unusual condition amongst physicians especially if the patient hails from an area endemic for filariasis.